Evaluating the Effectiveness of Collaboration in Water Resources Planning in California: A Case Study of CALFED - Catherine Marie Hudzik (University of California, Institute of Urban and Regional Development (IURD), 2003)
This thesis examines the collaborative processes used by the CALFED Operations Group (Ops Group) and the outcomes achieved by these processes. The CALFED Bay Delta Program is a complex partnership of over 20 state and federal agencies that seeks to balance competing needs and interests in the Sacramento-San Joaquin Delta. The Ops Group coordinates the operations of the two large water export projects in the south Delta - the Central Valley Project (CVP) and State Water Project (SWP) - with environmental and water quality regulations. Participants in the Ops Group were brought together by a conflict between environmental protection and water supply reliability. Fish populations were declining, while actions taken under the Endangered Species Act threatened the stability of the water supply. Through collaboration, dialogue, and detailed modeling of the system, the Operations Group was able to overcome decades of mistrust, legal barriers, financial risks, and scientific uncertainty to develop new tools for managing the complex Delta water system. The Ops Group moved from a system of isolated bureaucratic decision making and prescriptive standards for protecting endangered fish in the Delta to a system based on cooperative real-time management, where minor modifications to the CVP and SWP were made on a daily basis based on real-time monitoring data. The program at the center of this breakthrough was the Environmental Water Account. The Environmental Water Account is a program that was designed to let the Operations Group maintain reliability in the SWP and CVP water supply while reducing the amount of water pumped out of the Delta when the pumps pose a danger to fish. It is too soon to tell whether the Ops Group and the Environmental Water Account have improved either fish populations or long-term water supply reliability. However, this thesis describes several notable achievements that Ops Group members would not have been able to accomplish without collaboration. Agency staff and stakeholders with a history of adversity were able to create positive working relationships and shared understandings of the Delta water system. The social capital and new institutional structures built by these processes have enabled the Ops Group to creatively deal with challenges that would have previously resulted in an impasse.
Keywords: 330